2018
DOI: 10.3727/152599518x15346132863157
|View full text |Cite
|
Sign up to set email alerts
|

Event Design in Outdoor Music Festival Audience Behavior (A Critical Transformative Research Note)

Abstract: This work, a conceptual forward-looking article, examines the management of audiences at music festivals now and indicates a critical maneuver of focus for the future. The theoretical objectives and conclusions of a body of work by Robertson-discussing and then proposing future models of festival leadership to support place and event sustainability-are applied to bodies of work by Hutton and colleagues, ranging from 2011 to 2017, and Brown and colleagues in 2012, 2013, and 2016. It is argued that a more holist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…For example, tickets ATTITUDINAL IMPACT AT MUSIC FESTIVALS 785 respect among some of its attendees. This factor is incredibly important for fan engagement in outdoor music festivals (Robertson et al, 2018a) and could be improved by focusing more on customer service through social media. For example, the Glastonbury Festival in 2017 had four festival accounts on Twitter of which @Glastoinfo, was one dedicated to customer service alone; it was a helpline account sharing on-site updates and providing support to people at the festival (GlastoInfo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, tickets ATTITUDINAL IMPACT AT MUSIC FESTIVALS 785 respect among some of its attendees. This factor is incredibly important for fan engagement in outdoor music festivals (Robertson et al, 2018a) and could be improved by focusing more on customer service through social media. For example, the Glastonbury Festival in 2017 had four festival accounts on Twitter of which @Glastoinfo, was one dedicated to customer service alone; it was a helpline account sharing on-site updates and providing support to people at the festival (GlastoInfo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is important for mass-gathering health research that hazards and risks are contained and proactively managed. 8 Currently, the majority of research relates to the biomedical outcomes at MGEs. This is not surprising given that mass-gathering medicine is still new and has grown from an initial proximity model (biomedical, environmental, and psychosocial).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the audience and how health messages can be communicated is an important part of health promotion 7,14 and can add to the civic responsibility of an event through community engagement mechanisms. 8 Currently during music festivals around the globe, health messaging is used to reach audience members, ranging from crowd control to avoid crushes to messages about looking after friends and drinking responsibly when alcohol is being served. 24 Health promotion not only reinforces healthy behaviors, but also promotes social cohesion and can improve health outcomes both in and out of the event.…”
Section: Health Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Despite Pines and Maslach's 37 tool being successfully used in Hutton, et al's study, 5 Turris, et al 19 found that objective measures of crowd mood are not yet well-developed for use in the mass-gathering context; "Crowd mobility and density are sometimes used as proxies for crowd mood or indicators of risk (qualitative)." 17 Evidence suggests that crowd mood can be influenced by factors such as type of music 20,21,42 or sporting rivalry. 22 Hutton, et al found that crowd mood at sporting events is influenced by the level of engagement with the event.…”
Section: Crowd Moodmentioning
confidence: 99%